Exploring novice EAP teacher’s self-reflection as a platform for professional development - Hidayati, Sari (Universitas Pendidikan Indonesia, 2018)
Novice English for Academic Purposes (EAP) teachers are inevitably confronted with complex issues in their first year of teaching. This is particularly relevant in Indonesia, where EAP teachers are graduates of English Education departments and have no initial preparation for their tasks of teaching EAP. Professional reflection has the potential to assist novice language teachers, particularly those who teach EAP, to negotiate complex aspects in their teaching practice. For this reason, this single case study explored one participant’s understandings of and experiences with self-reflection as a form of professional development. Data were garnered from a single semi-structured, open-ended interview. The findings of the study suggest that the participant made use of reflective practice to merge theory and practice and build a systematic inquiry to construct his professional identity, which led to evidence-based decision making processes. Further, professional reflection also assisted him in negotiating challenges and engage in problem solving processes. Finally, reflective practice enabled the participant to consider institutional provisions and expectations for teacher professional development, which showcased his needs for professional development as a novice teacher.